-9z+7=-11

Simple and best practice solution for -9z+7=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9z+7=-11 equation:


Simplifying
-9z + 7 = -11

Reorder the terms:
7 + -9z = -11

Solving
7 + -9z = -11

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -9z = -11 + -7

Combine like terms: 7 + -7 = 0
0 + -9z = -11 + -7
-9z = -11 + -7

Combine like terms: -11 + -7 = -18
-9z = -18

Divide each side by '-9'.
z = 2

Simplifying
z = 2

See similar equations:

| 4.5(x)-20=88 | | 2z=1/2 | | n/7+9=13 | | -3n+5=-10 | | 25x-2(4x+100)= | | y^4-11y^2+18=0 | | x/x^2-5x-14=7/x-7-2/x+2 | | -62=-4x-5x+10 | | z^5-4+2i=0 | | 6(x+1)-2(y-5)=15 | | (4x^4+2x^2-3x+5)/x^2-7 | | 2*7x=-203 | | 11(x)=-25 | | 2x+2+x+4=-12 | | 2x/a+9x/b=c | | -5.50(x-2)=-46.75 | | x/.50=-5 | | -5.50(x-20)=-46.75 | | (8x+3y+67)/sqrt(8^2+3^2) | | -2.20x-11.20=29.40 | | -7y=14x-21 | | 3/4k-4=3 | | 3(2x+15)=108 | | 3(9)-3=18 | | 3/8*x=6 | | 1=1+4v-4v | | 7.5(x)-24=62.25 | | 3/8timesd=6 | | 3(z+7)=30 | | 0=x^2+4x-496 | | 5x-3(-4)=-2+5x-4 | | 6/-7+6/5 |

Equations solver categories